The genus Perissopalla Brennan and White, 1960 (Trombidiformes: Trombiculidae) in Brazil: Redescriptions, new localities, and host records with the first molecular data for the genus - Bassini-Silva, Ricardo [UNESP]; Almeida, Beatriz Rocha [UNESP]; Jacinavicius, Fernando de Castro; Lourenço, Elizabete Captivo; Welbourn, Cal; Ochoa, Ronald; Famadas, Katia Maria; Barros-Battesti, Darci Moraes [UNESP] (Elsevier, 2024)
The genus Perissopalla Brennan and White (Trombidiformes: Trombiculidae) is currently represented by ten species with three from Brazil: Perissopalla barticonycteris Brennan, Perissopalla ipeani Brennan, and Perissopalla tanycera Brennan. In the present study, these three species are redescribed and illustrated based on the types and additional non-type specimens. New host and locality records for P. ipeani and P. tanycera are included. Additionally, a partial sequence for the 18S rRNA gene for P. ipeani was provided.
Keywords: Bats; Chiggers; Ectoparasites; South America; Taxonomy